STUDENT LEADERSHIP DEVELOPMENT: INTEGRATING POTENTIAL, KNOWLEDGE, AND LOYALTY - Azahar, Ridho; Syahri, Alfi; Indah, Nurliyah; Irawati, Fitri (As-Sulthan Journal of Education, 2025)
The development of personal potential, understanding the urgency of science, and values of loyalty to the roles and responsibilities of students are important components in shaping character and individual competencies in higher education. This study aims to examine the effectiveness of a student leadership development training programme integrated with an approach that strengthens personal potential, mastery of science, and values of loyalty in improving the cognitive and affective competencies of participants. The research method employs a quantitative approach with a one-group pre-test and post-test design involving 90 students as respondents. Evaluation instruments consisting of pre-tests and post-tests were analysed using the Kolmogorov-Smirnov normality test, paired sample t-test, and one-sample t-test. The analysis results indicate that the data is normally distributed (p = 0.200), there was a significant difference between pre-test and post-test scores (t = -9.401, p = 0.000), and post-test scores were also significantly higher than the reference value (t = 3.933, p = 0.000), with an average increase of 19.83 points. These findings indicate that training that integrates aspects of self-potential, knowledge, and student loyalty values is proven to be effective in significantly improving understanding and skills.